Interviewing Practices, Conversational Practices, and Rapport: Responsiveness and Engagement in the Standardized Survey Interview. Issue 1 (August 2016) - Garbarski, Dana; Schaeffer, Nora Cate; Dykema, Jennifer
"Rapport" has been used to refer to a range of positive psychological features of an interaction, including a situated sense of connection or affiliation between interactional partners, comfort, willingness to disclose or share sensitive information, motivation to please, and empathy. Rapport could potentially benefit survey participation and response quality by increasing respondents' motivation to participate, disclose, or provide accurate information. Rapport could also harm data quality if motivation to ingratiate or affiliate causes respondents to suppress undesirable information. Some previous research suggests that motives elicited when rapport is high conflict with the goals of standardized interviewing. The authors examine rapport as an interactional phenomenon, attending to both the content and structure of talk. Using questions about end-of-life planning in the 2003–2005 wave of the Wisconsin Longitudinal Study, the authors observe that rapport consists of behaviors that can be characterized as dimensions of responsiveness by interviewers and engagement by respondents. The authors identify and describe types of responsiveness and engagement in selected question-answer sequences and then devise a coding scheme to examine their analytic potential with respect to the criterion of future study participation. The analysis suggests that responsive and engaged behaviors vary with respect to the goals of standardization; some behaviors conflict with these goals, whereas others complement them.